2015
DOI: 10.4103/2224-3151.206619
|View full text |Cite
|
Sign up to set email alerts
|

The validity of self-reported helmet use among motorcyclists in India

Abstract: Observed helmet use is low in Hyderabad, yet a larger proportion of motorcyclists claim to always wear a helmet, which suggests that observational studies can provide more valid estimates of helmet use. Interview findings suggest that a combination of increased enforcement, targeted social marketing and increased supply of standard helmets could be a strategy to increase helmet use in Hyderabad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 5 publications
0
21
4
Order By: Relevance
“…Any deviation from this leads to lower protection and increased risk and severity of head injury [11]. Earlier road side observational studies assessed any helmet, standard, full-face, and proper helmet use [12][13][14][22][23][24]. None of the studies specifically measured the prevalence of effective helmet use (standard, full-face and firmly fastened).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any deviation from this leads to lower protection and increased risk and severity of head injury [11]. Earlier road side observational studies assessed any helmet, standard, full-face, and proper helmet use [12][13][14][22][23][24]. None of the studies specifically measured the prevalence of effective helmet use (standard, full-face and firmly fastened).…”
Section: Discussionmentioning
confidence: 99%
“…If more than one motorcycle was passing at the same time, data was captured for the motorcycle that is closest to the side of the road. Validated data collection formats developed by Wadhwaniya et al [13] were adapted for recording the observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-reported and observed rates of wearing helmets were nearly 65% and 29%. [ 22 ] The difference in the rates observed may be due to the different study settings and study design. Nearly, 91% of them used right quality helmet with ISI mark, 87.9% used well-fitted helmets, 79.5% firmly fastened the chin straps of their helmets, and 78.3% used full face helmet in the present study, and similarly, Kulanthayan et al in Malaysia reported that 54.4% used helmets properly in which a properly used safety helmet was defined as a helmet which was worn with the strap correctly fastened.…”
Section: Discussionmentioning
confidence: 99%
“…Women are seen as the moral flag bearers and this has historically conditioned the image of the ideal woman, as being of shy nature, having a subdued character, speaking silently and a host of other traits. 'Socially desirable responding' [195] has been shown to under report or over report. Contraceptive methods are not just 'things-inthemselves' They cannot be separated from the social, political, and economic contexts in which they are utilized [196].…”
Section: Methodological Approach (M) Findings (F) Recommendations Amentioning
confidence: 99%